Role of typical soil particle‐size distributions on the long‐term corrosion behavior of pipeline steel. Issue 5 (22nd January 2016) - He, B.; Han, P. J.; Hou, L. F.; Lu, C. H.; Bai, X. H.
Abstract : The electrochemical behavior of X70 pipeline steel in a 1.5 wt% NaCl sandy soil environment with two typical particle size distributions (PSD), continuous gradation (CG), and gap gradation (GG) was investigated using electrochemical measurements, scanning electron microscopy (SEM), and X‐ray diffraction (XRD). The results showed that, as the burial time increased, the corrosion rate of X70 pipeline steel increased in the initial corrosion stage, decreased at an intermediate stage, and then increased in the final stage in these two typical soil PSD environments. However, compared with the soil PSD pertaining to the CG environment, the corrosion rate of steel increased significantly in the GG environment, as evinced by the severe corrosion spots observed on the steel surface, attributed to the fact that, in the soil PSD for the GG environment, both the extent of liquid dispersion, and the number of galvanic cells increased, accelerating the cathodic step, i.e., oxygen‐reduction reaction in the three‐phase boundary (TPB) zone, and anodic step, i.e., the metal dissolution stage, of the X70 pipeline steel corrosion process, respectively. Both the anodic and cathodic processes were activation controlled. Thus, the corrosion of X70 pipeline steel was considerably dependent on the soil PSD in sandy soil environments. Abstract : The electrochemical behavior of X70 pipeline steel in a 1.5 wt% NaCl sandy soil environment with two typical particle size distributions (PSD), continuous gradation (CG), and gap gradation (GG) was investigated. Compared with the soil PSD pertaining to the CG environment, the corrosion rate of steel increased significantly in the GG environment, as evinced by the severe corrosion spots observed on the steel surface.